State Aid and Competition in Banking: the Case of China in the Late Nineties - Xiaoqiang Cheng; Patrick Van Cayseele (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2009)
Many contributions to the literature on competition in banking use the Panzar and Rosse test (1987). This test encompasses a variety of market outcomes assuming firms maximize profits. However, when applied to the banking industry, this assumption may not be always valid as banks sometimes may carry social objectives or aim to be systemic players so as to be 'too big to fail'. This then motivates different objective functions, departing from profit maximization. We present a reduced firm model where banks can pursue other goals than profit maximization. This allows us to test for behavioral changes of banks over time. Our model provides a framework to evaluate whether moral hazard issues may plague banks receiving state aid, which concerns greatly the recent debate on government intervention in financial markets during the global financial crisis in 2008. To test the impact of state aid, we examine a natural experiment in the banking sector in China in the 1990s. We cannot reject that the possibility of receiving state aid triggers moral hazard prone conduct.
Keywords: G01; G21; G28; L21; 330; State Aid; banking industry; Panzar-Rosse model; Moral Hazard; To Big To Fail; Bank; Wettbewerb; Subvention; Moral Hazard; Theorie; Öffentliche Bank; China